EVALUASI KEBERLANJUTAN BUMDESA BERDASARKAN KINERJA KEUANGAN (STUDI PADA BUMDESA SEJAHTERA ABADI KABUPATEN PAMEKASAN) - Putri Ananta Rahayu; Aprilina Susandini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to determine the sustainability level of BUMDes Sejahtera Abadi in Pamekasan Regency based on financial performance measured through four key ratios: profitability, liquidity, activity, and solvency during 2020–2024. This research applies a descriptive quantitative method with a case study approach. The data used consist of financial statements, including the balance sheet and income statement and interview. The results show that profitability and activity ratios are in the healthy category, indicating good performance in generating profits and utilizing assets efficiently. The solvency ratio is also healthy, reflecting a strong financial structure with low debt dependency. However, the liquidity ratio is unhealthy, indicating limited short-term payment ability. Overall, BUMDes Sejahtera Abadi demonstrates fair financial sustainability, though improvements in cash management are needed to strengthen short-term stability